Pengaruh Pemanfaatan Teknologi Informasi, Peran Perangkat Desa, Dan Kejelasan Sasaran Anggaran Terhadap Akuntabilitas Pengelolaan Dana Desa Di Kecamatan Kerambitan - Yudha Wardana; Anantawikrama Tungga Atmadja (JIMAT (Jurnal Ilmiah Mahasiswa Akuntansi) Undiksha, 2022)
This study aims to determine the effect of the use of information technology, the role of village officials, and the clarity of budget targets on the accountability of village fund management. This research is a type of quantitative research with many respondents as many as 119 village officials in the Kerambitan District. Data obtained by distributing questionnaires directly. The sample was selected using criteria with purposive sampling method, namely the village apparatus consisting of the village head, village secretary, village head, section head, staff and regional head. The data used is primary data in respondents' answers and processed using SPSS Version 20. The results showed that the use of information technology, the role of village officials, and the clarity of budget targets had a positive and significant impact on the accountability of village fund management in the Kerambitan District. Keywords: information technology, village apparatus, budget targets, accountability